Rebel cowboy - Helm, Nicole (Helm, Nicole. Big Sky cowboys., 2016)
For hotshot NHL star Dan Sharpe, hockey isn't just his job, it's his everything. But when claims of cheating get him bounced from the ice, he finds himself feeling lost. Everyone thinks he's crazy for taking on his grandfather's ramshackle Montana ranch, but, hey, he's Dan Sharpe: How hard can it be? As it turns out? Plenty hard. Mel Shaw has been fighting tooth and nail to keep her family from falling apart. The last thing she needs is a distraction, but taking a job as some city slicker's consultant may be her only chance to save the land she loves. She never expected someone like Dan to come roaring into her life, and it doesn't take long for Mel to realize this hockey star turned cowboy has the power to upend her carefully ordered world--and heart---for good.